1996
DOI: 10.1002/(sici)1096-9861(19960729)371:3<461::aid-cne8>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunomicroscopy of neurofilaments in chromaffin cells of the adult bovine adrenal gland

Abstract: Neurofilaments (NFs) represent a class of intermediate filaments which are highly specific for neurons. The most abundant of the native NFs is the 68 kD subunit (NF-L). Chromaffin cells of the adrenal medulla express NF subunits under culture conditions. However, NF expression in situ is questionable. It has been reported that as chromaffin cell precursors mature and begin to express catecholamine-synthesizing enzymes, their neuronal traits are extinguished and they become endocrine-like cells. This study repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Even when previous studies demonstrated that pituitary cells in culture can maintain their functional differentiation for several weeks, and sometimes for months (17), it could be argued that the synthesis of neuronal markers could reflect an anomalous condition resulting from tissue dissociation or culture conditions. In this regard, it should be mentioned that adrenal chromaffin cells, which do not express NFs in situ , can express them under culture conditions (18). To rule out this possibility, NF68 immunolabelling was conducted in 5 µm‐thick sections of intact pituitary glands.…”
Section: Resultsmentioning
confidence: 99%
“…Even when previous studies demonstrated that pituitary cells in culture can maintain their functional differentiation for several weeks, and sometimes for months (17), it could be argued that the synthesis of neuronal markers could reflect an anomalous condition resulting from tissue dissociation or culture conditions. In this regard, it should be mentioned that adrenal chromaffin cells, which do not express NFs in situ , can express them under culture conditions (18). To rule out this possibility, NF68 immunolabelling was conducted in 5 µm‐thick sections of intact pituitary glands.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of adult bovine adrenal medulla that has been reported to express NF-L immunoreactivity (Yang et al 1996), based on the data currently available chromaffin cells seem devoid of a network of known IFs, not displaying detectable levels of vimentin, neurofilaments or cytokeratins (Ehrlich et al 1994;Kameda 1996;Quintanar 2000). For this reason the demonstration of in situ expression of nestin within adult rat adrenomedullary cells appears of particular interest.…”
Section: Discussionmentioning
confidence: 99%